2002
DOI: 10.1111/j.1346-8138.2002.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Cathepsin L and Cystatin A in Normal Skin and Skin Tumors

Abstract: Cathepsin L, a cysteine proteinase, and cystatin A, an inhibitor of cysteine proteinases, are thought to regulate the invasion and metastasis of malignant cells. In this study, the expression of cathepsin L and cystatin A in skin tumors was investigated immunohistochemically in order to examine the relationship between these two enzymes in the pathophysiology of malignant cells. Formalin-fixed and paraffin embedded specimens from normal skin, seborrheic keratoses, and squamous cell carcinomas were reacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Cystatin A shows more potent inhibitory activity against proteolytic activity of Der p 1 than other cystatins, including cystatin M/E, 30 and is strongly immunostained in the granular layer and moderately in the cornified and spinous layers in normal skin. 25 We also found that cystatin A was secreted into the culture supernatant of normal keratinocytes. Cystatin A purified from sweat was stable, even though it interacted with active Der p 1 or Der f 1 (unpublished observation).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cystatin A shows more potent inhibitory activity against proteolytic activity of Der p 1 than other cystatins, including cystatin M/E, 30 and is strongly immunostained in the granular layer and moderately in the cornified and spinous layers in normal skin. 25 We also found that cystatin A was secreted into the culture supernatant of normal keratinocytes. Cystatin A purified from sweat was stable, even though it interacted with active Der p 1 or Der f 1 (unpublished observation).…”
Section: Discussionmentioning
confidence: 95%
“…At least 5 cysteine protease inhibitors, cystatin A (stefin A), 24,25 cystatin M/E, 26 the prosequence of cathelicidin, 27 SCCA1, and SCCA2, 7,28 exist on or are inducible in human skin. The first report on the inhibitory activity of sweat was by Yokozeki et al, 29 who isolated an inhibitor from sweat with minimal epidermal contamination by means of affinity purification with a papain-coupled column, although they did not determine the identity of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…protein turnover of cells, apoptosis and matrix remodelling, we expected positive staining in IHC. Two reports by other groups showed Cat L to be expressed diffusely in all layers of the epidermis (27,28). This might result from the fact that the source of our normal skin sections is tissue obtained from plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…By immunostaining, Cat L, one of the proteinases targeted by hurpin, was also found expressed in normal skin (23). Interestingly, Western blot analysis showed that the most abundant form in normal skin is the inactive precursor of this proteinase (24).…”
Section: Discussionmentioning
confidence: 99%
“…Besides inactivation by hurpin and SCCAs, Cat L (as well as Cat B) is also inhibited by other endogenous cysteine proteinase inhibitors known as cystatins (31). Immunohistochemical localization of Cat L and cystatin A showed strong expression in normal skin and seborrheic keratosis, whereas expression was lower in well‐differentiated SCC and negative in undifferentiated SCC (23). Another cystatin, M/E, was found to be expressed in the stratum granulosum in normal skin (32).…”
Section: Discussionmentioning
confidence: 99%